2021
DOI: 10.1021/acs.est.1c01618
|View full text |Cite
|
Sign up to set email alerts
|

Persulfate Oxidation of Sulfamethoxazole by Magnetic Iron-Char Composites via Nonradical Pathways: Fe(IV) Versus Surface-Mediated Electron Transfer

Abstract: Despite the vital roles of reactive radical species in the coupled iron–carbon composite/persulfate (PS) system for eliminating pollutants, nonradical contributions are typically overlooked. Herein, we developed two efficient magnetic iron–char composites via low-temperature (BCFe-400) and high-temperature (BCFe-700) pyrolysis. The two composites activated PS through nonradical pathways for sulfamethoxazole (SMX) degradation. In the BCFe-400/PS system, high-valent iron Fe­(IV) was the dominant active species f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(50 citation statements)
references
References 47 publications
3
47
0
Order By: Relevance
“…Recently, it was demonstrated that high-valent iron-oxo species played a role in the PMS-based oxidation process when iron-containing materials were used as the catalysts. 36,61,62 Similar to the case reported previously, 36 k app for CBB removal decreased in the presence of PMSO (Fig. 4a).…”
Section: Reaction Mechanismsupporting
confidence: 90%
“…Recently, it was demonstrated that high-valent iron-oxo species played a role in the PMS-based oxidation process when iron-containing materials were used as the catalysts. 36,61,62 Similar to the case reported previously, 36 k app for CBB removal decreased in the presence of PMSO (Fig. 4a).…”
Section: Reaction Mechanismsupporting
confidence: 90%
“…HA was apt to compete with organic contaminants for SO 4 •– since HA could be readily scavenged by SO 4 •– at a rate constant of 6.8 × 10 3 L·mg C –1 s –1 . In contrast, the degradation of organic contaminants by Fe­(IV) would be slightly influenced by HA because of the inert reactivity of Fe­(IV) toward HA. The degradation of phenol was mainly ascribed to Fe­(IV), whereas Fe­(IV) and SO 4 •– contributed almost equally to the degradation of estradiol (Figure d). Therefore, the presence of HA had a negligible effect on the degradation of phenol but inhibited the degradation of estradiol in the rapid oxidation stage of the Fe­(II)/PMS process.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5 F, the open-circuit potential (OCP) of SA-Cu-NC sharply rises with the addition of PMS and gradually reaches a plateau (potential of the SA-Cu-NC+PMS∗ complex). After the addition of BPA, electron transfer process of BPA to SA-Cu-NC+PMS∗ complex results in a decline of OCP, accompanied by the oxidation of BPA and reduction of PMS ( Liang et al., 2021 ; Ren et al., 2022 ; Tan et al., 2020 ). In contrast, the potential of NC increases slightly upon the addition of PMS, and the subsequent addition of BPA causes an increase in the equilibrium potential.…”
Section: Resultsmentioning
confidence: 99%